Metastasizing "benign" cutaneous fibrous histiocytoma: a clinicopathologic analysis of 16 cases - Doyle, Leona A; Fletcher, Christopher D M (The American journal of surgical pathology, 2013)
Cutaneous fibrous histiocytoma (FH) is considered a benign tumor; however, certain types of FH have been shown to have a tendency for local recurrence, and there are rare reported cases of metastasis. In this study, 16 cases of morphologically benign FH with locoregional or distant metastasis were identified in consult files. Pathologic features of primary, recurrent, and metastatic tumors, as well as clinical outcome, were evaluated. Nine were male and 7 were female patients; mean age was 42 years (range, 3 to 68 y). Primary tumors arose on the leg in 5 patients, buttock in 1, trunk in 3, shoulder in 3, neck in 2, and finger in 1. The primary site in 1 case was unknown. Fifteen primary tumors available for review involved the dermis; 6 extended into the superficial subcutis. Tumor size ranged from 1 to 5 cm (median 3.2 cm). Histologically, primary tumors showed characteristic features of FH, being composed in most cases of a polymorphous population of bland spindle and histiocytoid cells in a mixed storiform and fascicular growth pattern with admixed foam cells, multinucleate cells, and inflammatory cells in varying proportions. Histologic variants included 11 cellular (2 with mixed atypical and cellular features), 2 aneurysmal, 1 atypical, and 1 epithelioid type. All tumors showed entrapment of hyalinized collagen bundles. Mitotic activity ranged from <1 to 13/10 HPF. Focal necrosis was seen in 1 primary tumor. Ten patients had local tumor recurrence; 4 patients had multiple local recurrences. Time to first recurrence ranged from 6 weeks to 13 years. The local recurrences of 1 tumor showed increased cytologic atypia, but recurrences were otherwise morphologically similar to primary tumors. Metastases occurred 0 to 180 months after diagnosis (median 17 mo) and involved the lungs (12 patients), lymph nodes (8), soft tissues (6), and liver (1). Five patients developed multiple satellite nodules in the region of the primary tumor. Metastases were morphologically similar to the primary tumors. So far, 6 patients died of disease, with a median time to death of 64 months (range, 10 to 168 mo). Four patients are alive with metastatic disease. Two patients are disease free at last follow-up, and 1 patient died of unrelated disease. Metastasis of morphologically benign cutaneous FH is an extremely rare but clinically aggressive event. Primary tumors tend to be large and cellular, but aggressive behavior cannot be predicted on morphologic grounds alone; however, early or frequent local recurrence may warrant closer clinical follow-up.